Caring for "incurables": the 150th anniversary of the Royal Hospital for Neuro-Disability, Putney. Issue 945 (14th July 2004) - Cook, G C
Abstract : The Royal Hospital for Incurables (RHI), now known as the Royal Hospital for Neuro-Disability and situated on West Hill, Putney, was founded by Andrew Reed DD exactly 150 years ago. The RHI was thus the pioneer in modern times of long stay institutions for the sick and dying. It became one of the great Victorian charities, and remained independent of the National Health Service, which was introduced in 1948. Originally the long stay patients suffered from a multiplicity of diseases; in recent years chronic neurological disease has dominated the scenario. This institution has also become a major centre for genetic and trauma-associated neurological damage, and rehabilitation.